Perlindungan Hak Terdakwa dan Korban Salah Tangkap Pelaku Tindak Pidana Terorisme dalam Sistem Peradilan Pidana - Nugraha, Muhammad Iqbal; Priyambodo, Mas Agus (FOCUS, 2023)
Almost all criminal law experts and criminologists say that the crime of terrorism is an extraordinary crime and the judicial process is different from ordinary crimes. Due to the extraordinary nature of this crime, almost all countries use special laws to deal with criminal acts of terrorism. The criminal act of terrorism is an extraordinary crime which is not easy to disclose, besides that terrorism is one of the crimes that has penetrated the territorial boundaries of a country and is a crime of violating human rights (extra ordinary crime). However, in eradicating criminal acts of terrorism, law enforcement officers must uphold human rights. Terror suspects or suspects are human beings who have human rights that we must respect. This means that they must also be treated like other human beings, whose rights as human beings must be fulfilled.